##### Ads

related to: 1

(

**1**/ 7)^(-**1**) = 7. A negative exponent is defined as a reciprocal so that it fits in with the rules for exponents, one of which is: x^a * x^b = x^(a + b). x^**1*** x^(-**1**) = x^0 =**1**Hence x^(-**1**) =**1**/ x.**1**Answers · Education & Reference ·**1**5/02/20**1**0**1**/3=0.33333... 3 x 0.3333...=0.999... 3 x (**1**/3)=**1**Therefore: 0.999....=**1**It's just the nature of ...9 Answers · Education & Reference · 23/

**1**0/20072x^2 - 3x +

**1**= (2x -**1**)(x -**1**) Notice that the terms on the left hand side of each... on the right hand side of each bracket are the factors of**1**(that is -**1*** -**1**=**1**) and that 2x * (-**1**) + x * (-**1**) = -2x - x = -3x and that...3 Answers · Education & Reference · 22/03/2009

**1**.[(**1**+cosx)/(sinx)]=-**1**cosecx + cotx = -**1**...............(**1**) [**1**/sinx = cosecx and cosx/sinx = cotx] We know that cosec^2x - cot^2x =**1**( it is a formula) so (cosecx + Cotx)(cosecx - cotx) =**1**..................(2) Now from (**1**...3 Answers · Education & Reference ·

**1**9/0**1**/20**1****1**√6 / (√2) -

**1**multiply top & bottom by the conjugate of the bottom: √6(√2 +**1**) / (√2 -**1**)(√2 +**1**) = (√**1**2 + √6) / (2 -**1**) = 2√3 + √6 that's it! ;)4 Answers · Education & Reference ·

**1**2/03/20**1**2...to do this addition problem is to first add the whole numbers (

**1**and 2). Next add the fractions (3/8 and**1**/4). Doing so we...3 Answers · Education & Reference · 05/

**1**2/20**1**0**1**. make it = to 0**1**/4x-**1**=0 2. add**1**to both sides**1**/4x=**1**3. multiply the fraction by the reciprocal to get a whole number to both sides. (4)**1**/4x=**1**(4) 4. solve! x=44 Answers · Education & Reference ·

**1**5/**1**2/2008((

**1**/x+h)-(**1**/x))/h [(x-x-h)/(x+h)]***1**/h -h/h(x+h) -**1**/(x+h)2 Answers · Education & Reference ·

**1**0/**1**0/20**1**2

##### Ads

related to: 1